2014
DOI: 10.1002/jcp.24819
|View full text |Cite
|
Sign up to set email alerts
|

p27 and Leukemia: Cell Cycle and Beyond

Abstract: Cell division is the foundation to development and the regulation of cell cycle progression is therefore of paramount importance to the living organisms. Primary control of cell cycle is achieved by an array of cyclins and cyclin dependent kinases (CDKs). The functions of these cyclin-CDK complexes are again regulated by a host of cyclin dependent kinase inhibitors (CDKI). Till date CDKIs are broadly classified into two groups-INK4 family (p15, p16, p18, and p19) and the cip/kip family (p21, p27, and p57). Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 130 publications
0
35
0
Order By: Relevance
“…However, annexin V/DAPI assay measured at day 4 and day 7 demonstrated that ZNF521 knockdown did not caused increased apoptosis (Figure 2D), suggesting that ZNF521 may be involved in proliferation and differentiation of MLL -rearranged cells rather than in cell survival. To substantiate this hypothesis, GFP-sorted transduced THP-1 and ML-2 cells were collected on glass slides by cytospin and stained with antibodies against p21 (CDKN1A) and p27 (CDKN1B) cell cycle inhibitors [22]. At day 7, we observed an increase of both p21 and p27 protein expression in ZNF521 knockdown cells, suggesting a prolonged G1/S transition as the main reason for the aforementioned cell cycle arrest (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 89%
“…However, annexin V/DAPI assay measured at day 4 and day 7 demonstrated that ZNF521 knockdown did not caused increased apoptosis (Figure 2D), suggesting that ZNF521 may be involved in proliferation and differentiation of MLL -rearranged cells rather than in cell survival. To substantiate this hypothesis, GFP-sorted transduced THP-1 and ML-2 cells were collected on glass slides by cytospin and stained with antibodies against p21 (CDKN1A) and p27 (CDKN1B) cell cycle inhibitors [22]. At day 7, we observed an increase of both p21 and p27 protein expression in ZNF521 knockdown cells, suggesting a prolonged G1/S transition as the main reason for the aforementioned cell cycle arrest (Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, we showed in vivo and in vitro that the rescuing effect of antibody blockade and SIS3 treatment was accompanied by suppression of p27 and enhancement of CDK2- cyclin E activities. It is well known that p27 is a CDK inhibitor, forming quaternary complexes with CDKs and thereby preventing cell cycle progression via cell-cycle arrest at the G1 phase 30 . Like CRP, TGF-β1 can also induce p27 protein expression while inhibiting CDK2 and cyclin E. 2022, 31 In the present study using ChIP assays we showed that Smad3, a key member of the TGF-β signaling family of molecules, was capable of binding to the p27 promoter in response to CRP stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Skp2 promotes the polyubiquitination of p27 Kip1 and thus accelerates p27 Kip1 degradation 30 , thereby decreasing levels of p27 Kip1 . Normally p27 Kip1 binds to complexes of cyclins with their respective cyclin-dependent kinases (Cdk), thus preventing cyclin-Cdk complexes from phosphorylating their substrates 31 . Importantly, p27 Kip1 impairs the function of cyclin D-Cdk4/6 complexes 31 that are primarily responsible for promoting cell-cycle progression in G1 phase of the cell cycle 32, 33 .…”
Section: Introductionmentioning
confidence: 99%